E-102 Basilar artery occlusion with involvement of posterior circulation branches and associated functional outcome: a preliminary analysis of single center registry. (22nd July 2019) - Zafar, A; Suriya, S; Farooqui, M; Ikram, A; Ortega-Guiterrez, S; Torbey, M
Abstract : Introduction: Acute basilar artery occlusion (BAO) accounts for 1% of all ischemic strokes and is associated with high mortality and morbidity. The purpose of study was to analyze functional outcome of patients with BAO in relation to the location of occlusion, posterior circulation branches and time interval from last known well (LKW) to groin puncture. Methods: This is a descriptive, retrospective study from a single center database. We reviewed patients presenting with BAO or with symptomatic high grade stenosis in basilar artery at UNMH between 2007 and 2017. Data was collected on secured Redcap™ database. The imaging data was reviewed by two independent physicians separately. Patients with no available imaging or follow up data, and no identifiable BAO or high grade stenosis on vascular imaging, were excluded. The outcome was defined as 1–3 months modified Rankin Scale (mRS). All patients were divided into three group based on their follow up mRS. Patients with mRS 0–2, patients with mRS 3–5 and patients with mRS 6. Results: A total of 66 patients with stenosis or occlusion of posterior circulation presenting with acute ischemic stroke were identified. Out of 66, complete imaging review of 52 patients was completed. Out of 52, no BAO occlusion or high grade stenosis was identified in 11 patients on vascular imaging. In 8 patients, there was no follow up mRS score or baseline vascular imaging available. Thirty two patients were included in the final analysis, out of which, 10 patients were mRS 0–2 group, 6 patients were in mRS 3–5 group and 16 patient were in mRS 6 group (see Table 1). Mean age in both groups was 64.7, 51.6 and 69.2 years respectively with male predominance. Hypertension was the most common baseline comorbidity in all groups. In mRS 6 group, 37.5% had occlusion in vertebrobasilar junction. Thrombectomy was performed in 40%, 33.3% and 37.6% patients repectively. The last known well (LKW) to groin puncture time was increased in patients with mRS 6. Conclusion: This retrospective analysis of BAO database depicts that older age, presence of HTN, history of prior stroke, location of clot at vertebrobasilar junction, and absence of bilateral posterior communicating arteries is associated with higher mortality. Moreover, delayed time to groin puncture was also observed in patients with higher mortality. Large scale studies are needed to validate these findings. Disclosures: A. Zafar: None. S. Suriya: None. M. Farooqui: None. A. Ikram: None. S. Ortega-Guiterrez: None. M. Torbey: None.